2011
DOI: 10.1007/s10552-011-9880-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia

Abstract: HbA1c as compared with fasting plasma glucose is more strongly and independently associated with colorectal neoplasia. Further research is warranted to elucidate the value of HbA1c in stratifying risk of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Hsu et al (2012) found an increase of OR=1.25 in colorectal neoplasia for each percentage increase in HbA 1c level for men and women ( P =0.02). HbA 1c was not statistically significantly associated with colorectal adenoma, distal colorectal adenoma or advanced adenoma in two studies (Wei et al , 2006; Yang et al , 2010).…”
Section: Resultsmentioning
confidence: 85%
“…Hsu et al (2012) found an increase of OR=1.25 in colorectal neoplasia for each percentage increase in HbA 1c level for men and women ( P =0.02). HbA 1c was not statistically significantly associated with colorectal adenoma, distal colorectal adenoma or advanced adenoma in two studies (Wei et al , 2006; Yang et al , 2010).…”
Section: Resultsmentioning
confidence: 85%
“…There is increasing evidence that abnormal glucose metabolism is associated with an increased risk of colorectal cancer [51, 52]. There is an extensive body of research examining the relationship between diabetes and colorectal cancer, and findings have so far varied, with relative risks of colorectal cancer ranging from 1.2 to 2.8 in prospective cohort studies [48].…”
Section: Diabetes and Insulin Resistance And Colorectal Cancermentioning
confidence: 99%
“…Khaw et al examined the relationship between known diabetes and glycated haemoglobin (HbA1c) concentrations measured in 9,605 men and women and subsequent incident colorectal cancer after 6 years follow up in the European Prospective Investigation into Cancer-Norfolk Study [51, 52, 54]. Their main finding is that the risk of colorectal cancer increased after HbA1c concentrations above 7%.…”
Section: Diabetes and Insulin Resistance And Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations